Leber’s hereditary optic neuropathy companied with multiple-related diseases - Sun, Ming-ming; Zhou, Huan-fen; Sun, Qiao; Li, Hong-en; Liu, Hong-juan; Song, Hong-lu; Yang, Mo; Teng, Da; Wei, Shi-hui; Xu, Quan-gang (Frontiers in Human Neuroscience, 2022)
Objective: To elucidate the clinical, radiologic characteristics of Leber’s hereditary optic neuropathy(LHON) associated with the other diseases. Methods: Clinical data were retrospectively collected from hospitalised patients with LHON associated with the other diseases at the Neuro-Ophthalmology Department at the Chinese People’s Liberation Army General Hospital (PLAGH) from December 2014 to October 2018. Results : A total of 13 patients 24 eyes (10 men and 3 woman; mean age, 30.69 ± 12.76 years) with LHON mitochondrial DNA (mtDNA) mutations were included in the cohort. 14502(5)11778(4)11778&11696(1)12811(1)11696(1)3460(1).One patient was positive for aquaporin-4 antibody(AQP4-Ab) and two were positive for myelin oligodendrocyte glycoprotein antibody (MOG-Ab). Three patients associated with idiopathic optic neuritis (ON). Two patients with compression optic neuropathy. Three patients with the central nervous system(CNS) diseases. One patient with proliferative diabetic retinopathy(PDR) and one with idiopathic orbital inflammatory syndrome(IOIS). At onset, visual acuity(VA) in eighteen eyes was below 0.1, one eye was 0.5, five eyes was above 0.5, while VA in sixteen eyes was below 0.1 outcome, three eyes experienced moderate vision loss. MRI images showed T2 lesions and enhancement in nine patients who received corticosteroids treatment, additional immune modulators treatment was performed on two patients.None patient had relapse during the follow-up time. Conclusions: LHON can be companied with multiple related diseases especially different subtype of ON, which were also exhibited with IOIS and compression optic neuropathy for the first time in this cohort. This condition may be a distinct entity with an unusual clinical and therapeutic profile.